PREFACE. The 2nd Baltic Osseointegration Academy and Lithuanian University of Health Sciences Consensus Conference 6 - 7 September 2019, Kaunas, Lithuania - Gintaras Juodzbalys (eJournal of Oral Maxillofacial Research)
Baltic Ossoeintegration Academy (BOA) together with the Lithuanian University of Health Sciences (LSMU) and Universities from Europe and USA organized their second Consensus Conference (CC) devoted to the topic of "Post-Extraction Bone Remodelling and Alveolar Ridge Preservation". BOA - LSMU consensus development group (CDG) was seeking to review the dental literature on a topical area in dental implantology and to produce high-quality, unbiased evidence-based guidelines and consensus statement (CS). CDG as the responsible body formulated the task of developing CS devoted to the topic of "Post-Extraction Bone Remodelling and Alveolar Ridge Preservation" to Gintaras Juodzbalys (Lithuania). CS Panel members were invited by the chairman. They are representatives of Universities, experts in a field and made every effort to produce nonbiased, independent, evidence-based clinical practice guidelines. Panel members had no conflicts of interest and signed a Panel Member Agreement (PMA). Working groups were established and following clinically relevant topics suitable for consensus discussion were identified: 1. Biological aspects of tooth extraction, socket healing and indications for socket preservation (group leader: Gintaras Juodzbalys) [1]. 2. Extraction socket preservation methods and dental implant placement outcomes within grafted sockets (group leader: Pablo Galindo-Moreno) [2].